2013
DOI: 10.1007/s10584-013-0710-y
|View full text |Cite
|
Sign up to set email alerts
|

Climate policies can help resolve energy security and air pollution challenges

Abstract: This research assesses three key energy sustainability objectives: energy security improvement, climate change mitigation, and the reduction of air pollution and its human health impacts. We illustrate how the common practice of narrowly focusing on singular issues ignores potentially enormous synergies, highlighting the need for a paradigm shift toward more holistic policy approaches. Our analysis of a large ensemble of alternate energy-climate futures, developed using MESSAGE, an integrated assessment model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(81 citation statements)
references
References 16 publications
1
78
0
2
Order By: Relevance
“…In a similar vein, using a global chemical transport model, West et al (24) found that health cobenefits of climate measures would largely exceed the associated mitigation costs. Finally, McCollum et al (25) focus on synergies between climate policy and other policies. They point out that ambitious climate measures would reduce the costs of clean air policies and energy security measures by US$100-600 billion (0.1-0.7% of GDP) annually by 2030.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, using a global chemical transport model, West et al (24) found that health cobenefits of climate measures would largely exceed the associated mitigation costs. Finally, McCollum et al (25) focus on synergies between climate policy and other policies. They point out that ambitious climate measures would reduce the costs of clean air policies and energy security measures by US$100-600 billion (0.1-0.7% of GDP) annually by 2030.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure assessment studies that seek to measure human health impacts are evaluated at even finer resolutions (e.g., 1×1 km or at street or block level) (Zapata et al 2013). Although some integrated assessment models have linked energy projections with air quality to understand cobenefits of climate policies (e.g., McCollum et al 2013), the resolution of these models is at most 1x1°(approximately 111×111 km at the equator). Despite requests from policymakers, attempting to integrate air quality and energy models at a finer resolution may not be practical in terms of model development and computing time.…”
Section: Discussionmentioning
confidence: 99%
“…MAPS stands out for the applied contributions on co-benefits assessments in national policy processes in developing countries. The IPCC advances general concerns on the relationship between climate mitigation and SD, definitions and concepts, integrated assessment models, uncertainties and, very importantly, sectoral approaches including health and air pollution (Bell et al, 2008;IPCC, 2014;McCollum et al, 2013;Nemet, Holloway, & Meier, 2010;Riahi et al, 2012;Smith et al, 2009). …”
Section: Knowledge Network: Knowledge Holders and Their Ideasmentioning
confidence: 99%